UNPAID PARENTAL CAREGIVING AND EMPLOYMENT STATUS IN INDONESIA - Willy, Christopher; Afrizal, Rafa Fayza; Fabian, Irvel Christa; Samith, Muhammad Farras (Jurnal Ekonomi Kependudukan dan Keluarga, 2025)
This study examines the impact of unpaid parental caregiving on employment status and formal sector employment opportunities in Indonesia, using panel data from the 2007 and 2014 waves of the Indonesia Family Life Survey (IFLS). Propensity Score Matching (PSM) was applied to mitigate selection bias and estimate the Average Treatment effect on the Treated (ATT) for three caregiver categories: temporary, recent, and continuous. Results indicate that, after controlling for baseline characteristics, none of the caregiver categories significantly affected the probability of being employed or employed in the formal sector in 2014. The findings suggest that caregiving practices in Indonesia generally do not lead to labor market withdrawal but instead prompt adjustments in working hours or shifts to informal employment. Policy implications include the need for affordable and flexible care support services and strengthened protection for informal workers.